PENERAPAN PEMBELIAN TANAH DALAM RANGKA PENGADAAN TANAH UNTUK BANDARA - Nurdaiman, Taqiy; Al-Ansori, Huzaimah; Wachid Hasyim, Moch (Jurnal Magister Hukum Perspektif, 2023)
The application of land purchase/procurement in the context of land acquisition for the public interest of the airport whose land object is still in the effort to transfer rights to the PPJB stage needs to be studied. The formulation of the problem in this study, how is the process of purchasing land in the context of land acquisition for the public interest of the airport based on PP No. 19 of 2021, and what is the ownership status and legal protection for landowners who have been purchased by speculators up to the PPJB stage before the letter of determination of the location of land acquisition is issued by the government. The purpose of this study is to further examine the application of PP No. 19 of 2021 as a legal basis in land acquisition for development for the public interest of airports, and the suitability of its application with existing norms and positive laws in guaranteeing the rights of entitled landowners. The method used in this research is normative juridical with a statutory approach. The result of this research is that PP No.19 of 2021 has improved the previous law, it's just that there is no limit to the rules regarding eligibility standards regarding agencies to be able to apply for land acquisition, and the laying of location determinations which results in restrictions on the transfer of rights that are less effective, as well as the unclear application of article 139 so that the author concludes that this PP is still immature. Meanwhile, regarding the protection and ownership status of HAT on the right owner, adhering to the legal force of the PPJB which has the status of an underhand deed, the land rights remain with the seller, while the legal protection of the legal actions carried out, namely by making a new agreement as mandated in article 1233 of the Civil Code. Keywords: Land Procurement, Land Purchase, Speculators.